2008
DOI: 10.1208/s12249-008-9053-9
|View full text |Cite
|
Sign up to set email alerts
|

Permeation Studies of Indomethacin from Different Emulsions for Nasal Delivery and Their Possible Anti-Inflammatory Effects

Abstract: Abstract. The purpose of this research was to develop an emulsion formulation of indomethacin (IND) suitable for nasal delivery. IND was incorporated into the oil phases of oil in water (O/W) and water in oil (W/O) emulsions. For this purpose, different emulsifying agents (Tween 80, Span 80 and Brij 58) were used in two emulsion formulations. When the effects of several synthetic membranes (nylon, cellulose, cellulose nitrate) were compared with the sheep nasal mucosa, the cellulose membrane and sheep nasal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Huang et al (1995) showed that IND solutions could easily pass through the nasal mucosa in rats and enter the systemic circulation. In this study, nasal absorption was close to that obtained after per oral (po) dosing (Karasulu et al (2008)). Xylometazoline HCl (XYL) is applied topically to relieve nasal congestion associated with acute or chronic rhinitis, common cold, sinusitis, hay fever or other allergies.…”
Section: Introductionsupporting
confidence: 82%
“…Huang et al (1995) showed that IND solutions could easily pass through the nasal mucosa in rats and enter the systemic circulation. In this study, nasal absorption was close to that obtained after per oral (po) dosing (Karasulu et al (2008)). Xylometazoline HCl (XYL) is applied topically to relieve nasal congestion associated with acute or chronic rhinitis, common cold, sinusitis, hay fever or other allergies.…”
Section: Introductionsupporting
confidence: 82%
“…This percentage has risen to 20:35 ± 0:58 for NE. Although this alteration is not statistically significant (P > 0:05), but it seems as NEs are more viscous formulations than solutions, they result in elevated residence time of the drug in the nasal cavity [62]. In consequence of adding poloxamer, in situ gel NE showed a noticeable mucoadhesion percentage of 37:037 ± 2:32 (P < 0:001).…”
Section: Ex Vivo Mucoadhesion Studymentioning
confidence: 84%
“…Given that the absorption rate for the majority of drug substances is rapid, the degree of absorption relies on physiological factors like the nasal secretion rate, ciliary movement and metabolism (Table 7; Costantino et al, 2007;Karasulu et al, 2008;Kim et al, 2009;Cros et al, 2011;Wang et al, 2012a,b). The nasal secretion and ciliary movement can collectively termed as mucociliary clearance and fluctuate according to health conditions of individual.…”
Section: Challenges Related To Physiological and Pathological Aspectsmentioning
confidence: 99%